2008
DOI: 10.1111/j.1558-5646.2008.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Coalescent Analyses of Multiple Loci Support a New Route to Speciation in Birds

Abstract: A widely accepted paradigm is that sedentary Neotropical bird species are a reservoir that gives rise to temperate-tropical migratory species. Recently, an alternative theory has been proposed, that developmental plasticity can allow some individuals within a migratory species to establish a disjunct breeding range through loss of migration, thus facilitating the founding of a new sedentary species. We used mtDNA and two nuclear introns to perform coalescent analyses for two closely related New World oriole sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…There were six changes from sedentary to partially migratory, and three reversals from a partially migratory species to a sedentary one. Kondo et al (2008) studied two oriole (Icterus) sister species and found that, in contrast to the traditional paradigm, a short-distance migrant was derived from a long-distance migrant. At a more inclusive level in oriole phylogeny, Kondo & Omland (2007) used multistate ancestral state reconstruction of migration (coded as long-distance, short distance, partial migrants or sedentary), to examine patterns of migratory evolution in the New World orioles.…”
Section: Phylogenetic Mapping Of Migrationmentioning
confidence: 94%
“…There were six changes from sedentary to partially migratory, and three reversals from a partially migratory species to a sedentary one. Kondo et al (2008) studied two oriole (Icterus) sister species and found that, in contrast to the traditional paradigm, a short-distance migrant was derived from a long-distance migrant. At a more inclusive level in oriole phylogeny, Kondo & Omland (2007) used multistate ancestral state reconstruction of migration (coded as long-distance, short distance, partial migrants or sedentary), to examine patterns of migratory evolution in the New World orioles.…”
Section: Phylogenetic Mapping Of Migrationmentioning
confidence: 94%
“…But this seems unlikely considering the absence of Great Skuas from eastern Siberia and the (current) nonmigratory behavior of New Zealand skuas. However, migratory tendencies, or lack of them, can evolve amazingly rapidly and have been proposed as a special route to speciation (Berthold et al, 1992;West-Eberhard, 2003;Bearhop et al, 2005;Kondo et al, 2008). Additional (nuclear) markers may help to solve this mystery in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic labeling of the units involved in the process of differentiation is imperfect, but these and many other examples represent migratory lineages within which reproductive isolation has been achieved between sublineages; speciation has occurred in the presence of migration. Among some of these taxa-for example, Dendroica "petechia," Vireo "solitarius," Piranga (Burns 1998), and Baltimore Orioles (Icterus galbula) and Black-backed Orioles (I. abeillei) (Kondo et al 2008)-the mapping of migration onto the phylogenetic trees shows that some of the differentiation or speciation is correlated with a subgroup of the ancestral lineage dropping out of migration to establish resident, nonmigratory (or less migratory) breeding populations, usually in tropical or subtropical regions (Klein and Brown 1994, Johnson 1995, Burns 1998, cicero and Johnson 1998, Kondo et al 2008. Several sedentary caribbean species in the genus Vireo may also be found to be members of the V. "olivaceus" species group ( fig.…”
Section: Migrant Differentiationmentioning
confidence: 99%